PENGARUH TINGKAT PENDIDIKAN ORANG TUA SISWA DENGAN PRESTASI BELAJAR SISWA DI DESA LUMBAN SILINTONG - Rezeki, Ulfah Sari; Ristina, Heppy; Yohana, Katerina (JURNAL CURERE, 2023)
A nation's education can develop its country's progress and catch up with other countries. Parents are the first place to provide basic education, the first place to grow and develop. Factors that influence the success of the educational process are family environmental factors, school environment and community environment. Of these factors, one of the keys to education is the role of parents in the student's family environment as a driving force, an advisor and an example for their children, apart from being someone who loves, gives affection and is a place for their children to ask questions. It is parents who know the character and character of the child best so that it is more likely that the parents will know what the child wants. The way parents educate their children has a big influence on children's learning. The family is the first and foremost educational institution. Healthy families play an important role in education on a small scale, but are crucial for education on a large scale, namely the education of the nation, state and world. Based on this, it can be understood how important the role of the family in children's education. The way parents educate their children will affect their children's learning achievement. So that students can understand and have an interest in learning, parents need to pay attention to their children so they understand what their children need in order to improve their learning achievements. In reality, many parents still think that educational issues are the teacher's business, so the parent's responsibility to pay attention to their child's education disappears. Apart from parental attention, parental educational background can also have an influence on children's interest in learning, which in turn will influence children's learning achievement. Students' perceptions of their parents' education will influence their perception of the importance of education itself, which will influence their learning achievement. This is in accordance with the results of a study conducted by Pratiwi in Tangerang in 2015. The study was conducted on 80 class This is evidenced by the acquisition of tcount = 5.853 and Sig. 0.000 < 0.05. The variable level of parental education contributes 23.41% in improving the Indonesian language learning achievement of Health Vocational School students in Tangerang City